Determining the Probability of Unproductive Manipulations in Inland Intermodal Terminal Operations - Zajac, Mateusz; Rožić, Tomislav; Naletina, Dora (Promet - Traffic&Transportation, 2023)
The paper concerns the method of determining the probability of unproductive manipulations during operations, maintenance or repairs on an inland intermodal terminal. The method is mathematically based on the semi-Markov process. The developed method enables revision of unproductive manipulation frequency and duration. It provides an opportunity to analyse and change inland terminal operations so as to increase productivity.